2007
DOI: 10.1111/j.1745-4557.2007.00108.x
|View full text |Cite
|
Sign up to set email alerts
|

SENSORY CHARACTERISTICS OF EWE MILK CHEESE MADE WITH THREE TYPES OF COAGULANT: CALF RENNET, POWDERED VEGETABLE COAGULANT AND CRUDE AQUEOUS EXTRACT FROM CYNARA CARDUNCULUS

Abstract: This article reports on a study of the sensorial characteristics of ewe milk cheese (Los Pedroches) made with animal rennet and two types of coagulant obtained from the cardoon Cynara cardunculus. The cheeses made with rennet displayed a less odor intensity: pungent odor and acid odor; a less acid taste; and a slightly lighter color. They were harder and firmer, but less creamy than those made with the vegetable coagulant (powdered vegetable coagulant [PVC] and crude aqueous extract [CAE] from C. cardunculus).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 25 publications
6
25
0
2
Order By: Relevance
“…In a previous study, it was observed that Murcia al Vino cheese made with animal rennet was significantly harder (P<0.01), more grainy (P<0.001), and less creamy (P<0.001) than the same cheese made using plant coagulant (Tejada et al 2006). Similar findings have been reported for ewe's milk cheeses made using vegetable coagulant from C. cardunculus, which were softer and creamier than those made using rennet (Tejada et al 2007). The intense level of proteolysis which occurred in cheeses made using vegetable protease hydrolyzed the casein network, creating a more homogeneous structure, thus prompting greater creaminess and softening of the cheese (Tejada et al 2007).…”
Section: Sensory Characteristicssupporting
confidence: 85%
See 1 more Smart Citation
“…In a previous study, it was observed that Murcia al Vino cheese made with animal rennet was significantly harder (P<0.01), more grainy (P<0.001), and less creamy (P<0.001) than the same cheese made using plant coagulant (Tejada et al 2006). Similar findings have been reported for ewe's milk cheeses made using vegetable coagulant from C. cardunculus, which were softer and creamier than those made using rennet (Tejada et al 2007). The intense level of proteolysis which occurred in cheeses made using vegetable protease hydrolyzed the casein network, creating a more homogeneous structure, thus prompting greater creaminess and softening of the cheese (Tejada et al 2007).…”
Section: Sensory Characteristicssupporting
confidence: 85%
“…Similar findings have been reported for ewe's milk cheeses made using vegetable coagulant from C. cardunculus, which were softer and creamier than those made using rennet (Tejada et al 2007). The intense level of proteolysis which occurred in cheeses made using vegetable protease hydrolyzed the casein network, creating a more homogeneous structure, thus prompting greater creaminess and softening of the cheese (Tejada et al 2007). Peshawari cheese made using GP received significantly higher (P<0.05) flavor scores than cheeses made using CR.…”
Section: Sensory Characteristicssupporting
confidence: 85%
“…As a result the ripening time required to attain typical sensory characteristics was shorter for cheeses made with PPC or CR/PPC. No significant differences were found for acid, salty and spicy taste (P > 0.05), as has been reported by Tejada et al (2007) in ewes' milk cheeses made with plant coagulant and with CR. Scores for bitter taste differed significantly (P < 0.05) between CR and PPC cheeses along the studied period.…”
Section: Sensory Evaluationsupporting
confidence: 59%
“…In studies by Hort et al (1997) and Tejada, Gómez, and Fernández-Salguero (2007), a direct correlation between proteolysis and creaminess was observed. Initial hydrolysis of bovine a s1 -casein by C. cardunculus proteinases occurs at Phe 23 -Phe 24 , cleavage of which causes a concomitant softening of cheese texture (O'Mahony et al, 2003).…”
Section: Sensory Evaluationmentioning
confidence: 77%
“…These cheeses are currently enjoying considerable commercial success, and are increasingly prized by the consumer for their soft, creamy texture and their characteristic exquisite flavour, sometimes slightly bitter but piquant. 2 Three proteinases of C. cardunculus L. have been isolated, purified, and partially characterised in terms of activity. 3 They are thus acidic proteinases belonging to the aspartic proteinase group called 'cynarases' or 'cyprosins'.…”
Section: Introductionmentioning
confidence: 99%